Molecular Epidemiology of Theileria annulata in Cattle from Two Districts in Punjab (Pakistan) - Parveen, Asia; Alkhaibari, Abeer Mousa; Asif, Muhammad; Almohammed, Hamdan I.; Naqvi, Zahra; Khan, Adil; Iqbal, Furhan (Mdpi, 2021)
Simple Summary Pakistan is a tropical country where climate is favourable for tick growth and hence its incidence of tick-borne diseases is high, affecting the output of the livestock sector. In the present study the infection rate of Theileria annulata, the causative agent of bovine theileriosis, was compared in apparently healthy cattle enrolled from two different regions in Pakistan. Parasite prevalence was found to be higher in Dera Ghazi Khan District than in Lodhran. The infection rate was higher in cattle that were infested with ticks and in those animals that were housed indoors at dairy farms with other animals. This prophylactic detection of parasite will help to design strategies to control tick and tick-borne diseases in study areas. The present study was designed to report the molecular prevalence of T. annulata in cattle blood samples collected from Punjab in Pakistan. A total of 428 cattle blood samples were collected from Districts Lodhran (n = 218) and Dera Ghazi Khan (n = 210). The prevalence of T. annulata was determined by the amplification of a fragment from its cytochrome b gene and parasite prevalence was significantly higher (p = 0.03) in the blood samples of cattle collected from Dera Ghazi Khan (70/210; 33%) as compared to Lodhran (52/218; 24%). Presence of T. annulata was also confirmed by the amplification of a fragment from their 30 kDa gene. The amplified PCR products of both genes were confirmed by DNA sequencing and these partial DNA sequences were submitted to GenBank. Phylogenetic analysis revealed that amplified partial gene sequences resembled previously reported T. annulata sequences in cattle from India, China, Iran, Tunisia, Turkey and Egypt. The incidence of T. annulata infection was higher in Sahiwal cattle (p = 0.04) than the other enrolled cattle breed from Dera Ghazi Khan. Female cattle from Lodhran (p = 0.02), while males (p = 0.02), animals housed in close compounds (p = 0.04), animals with a tick burden (p = 0.005) and farms with only cattle (p = 0.01) in Dear Ghazi Khan were found to be more susceptible to T. annulata infection. We recommend that large-scale tick and tick-borne disease control strategies be implemented in both districts under investigation, especially in Dera Ghazi Khan.
Keywords: Theileria annulata; cytochrome b gene; 30 kDa gene; epidemiology; phylogenetic analysis